Negative ion resonance states: the fock-space coupled-cluster way - Basumallick, Suhita; Sajeev, Y.; Pal, Sourav; Vaval, Nayana (Journal of Physical Chemistry A, 2020)
The negative ion resonance states, which are electron-molecule metastable compound states, play the most important role in free-electron controlled molecular reactions and low-energy free-electron-induced DNA damage. Their electronic structure is often only poorly described but crucial to an understanding of their reaction dynamics. One of the most important challenges to current electronic structure theory is the computation of negative ion resonance states. As a major step forward, coupled-cluster theories, which are well-known for their ability to produce the best approximate bound state electronic eigen solutions, are upgraded to offer the most accurate and effective approximations for negative ion resonance states. The existing Fock-space coupled-cluster (FSCC) and the equation-of-motion coupled-cluster (EOM-CC) approaches that compute bound states are redesigned for the direct and simultaneous determination of both the kinetic energy of the free electron at which the electron-molecule compound states are resonantly formed and the corresponding autodetachment decay rate of the electron from the metastable compound state. This Feature Article reviews the computation of negative ion resonances using the FSCC approach and, in passing, provides the highlights of the equivalent EOM-CC approach.

Shape resonance of sulphur dioxide anion excited states using the CAP-CIP-FSMRCCSD method - Basumallick, Suhita; Bhattacharya, Sumantra; Jana, Irina; Vaval, Nayana; Pal, Sourav (Molecular Physics, 2020)
We have studied the shape resonance of excited states of sulphur dioxide (SO2) anion by using the correlated independent particle Fock space multi-reference coupled cluster (CAP-CIP-FSMRCCSD) method augmented by complex absorption potential. These resonant states have been trapped experimentally in recent years by electron collision. In particular, we have investigated e(-)-SO2 scattering and computed the negative-ion resonance states of the anion responsible for the two resonances around 4.45 and 6.56 eV and compared the results with the existing experimental observations. From the computational results using the CAP-CIP-FSMRCCSD method, it has been observed that both the resonances near 4.45 and 6.56 eV result from A(1) symmetries. [GRAPHICS] .
Keywords: CAP augmented correlated independent particle (CAP-CIP-FSMRCCSD); complex absorption potential (CAP); coupled cluster; Fock space multireference coupled cluster (FSMRCCSD); shape resonance

Resonance study: effect of partial triples excitation using complex absorbing potential-based Fock-space multi-reference coupled cluster - Jana, Irina; Basumallick, Suhita; Pal, Sourav; Vaval, Nayana (International Journal of Quantum Chemistry, 2021)
Resonances are metastable states with finite lifetime. They play important role in physics, chemistry and biology. The theoretical calculation of resonance state is a challenging problem. In this paper we have studied the shape resonance of Be, Mg, N-2 and CO. We have used correlated independent particle approximation to the Fock space multi-reference coupled cluster singles-doubles with third-order triples (CAP-CIP-FSMRCCSD(T)) method augmented by complex absorption potential. The resonance energy and decay widths are obtained by solving a non-Hermitian eigen-value problem within FSMRCC framework. The effects of the lowest order triples on the resonance energy and decay are studied.
Keywords: complex absorbing potential; electron affinity; Fock‐ negative ion resonance; partial triples; space MRCC